Implementation of the CEFR in the rubrics of two main English Certificates: Cambridge FCE and Trinity ISE-II. Implementación del MCER en las rúbricas de dos principales certificados de inglés: Cambridge FCE y Trinity ISE-II - Lucía Fraga Viñas (Universidad de Las Palmas de Gran Canaria, 2021)
The Common European Framework of Reference (CEFR) was developed by the European Council with the intention of providing a comprehensive basis for the creation language syllabi and curriculum guidelines, together with the design of teaching materials, language certificates and instruments of assessment. The CEFR has been implemented in Spain through different education laws and has prompted the introduction of the communicative approach and the use of new instruments of assessment such as rubrics. Nonetheless, almost twenty years after the CEFR was passed, not many pieces of research have been conducted on how the Framework has been implemented. It is from this line where the current research stems as it intends to check how the CEFR has been adapted in the rubrics used for the assessment of the writing skill in two main English Certificates: the Cambridge Assessment English FCE and the Trinity College ISE-II. El Marco Común Europeo de Referencia (MCER) se desarrolló con el objetivo de promover una base común para la creación de currículos educativos y servir como guía en la elaboración de materiales didácticos, exámenes de certificación e instrumentos de evaluación. El MCER se ha implantado en España a través de diferentes leyes educativos y ha propiciado la introducción del enfoque comunicativo o nuevos instrumentos de evaluación como rúbricas. Sin embargo, casi veinte años después de la probación del marco, pocos son los estudios que han revisado de qué manera se ha adaptado el marco. Es aquí donde la presente investigación se sitúa, con el objetivo de comprobar cómo se ha implementado el MCER en las rúbricas para examinar la destreza escrita de dos de los principales certificados de inglés: el Cambridge Assessment English FCE y el Trinity College ISE-II